2021
DOI: 10.3390/v13081454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Infection and Cross-Species Detection of Equine Parvovirus-Hepatitis

Abstract: Since its first discovery by Arnold Theiler in 1918, serum hepatitis also known as Theiler’s disease has been reported worldwide, causing idiopathic acute hepatitis and liver failure in horses. Recent studies have suggested a novel parvovirus, named equine parvovirus hepatitis (EqPV-H), to be associated with Theiler’s disease. Despite the severity and potential fatality of EqPV-H infection, little is known about the possibility of developing chronic infections and putative cross-species infection of equine sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 31 publications
3
30
1
2
Order By: Relevance
“…In 2018, Divers et al reported EqPV-H for the first time in a case of Theiler's disease (i.e., equine serum hepatitis or idiopathic acute hepatic disease) [6] in the United States [1]. Theiler's disease is the most frequent cause of acute and probably fatal viral equine hepatitis [7][8][9]. This disease has been linked to EqPV-H infection, with or without the previous administration of equine biological products [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Divers et al reported EqPV-H for the first time in a case of Theiler's disease (i.e., equine serum hepatitis or idiopathic acute hepatic disease) [6] in the United States [1]. Theiler's disease is the most frequent cause of acute and probably fatal viral equine hepatitis [7][8][9]. This disease has been linked to EqPV-H infection, with or without the previous administration of equine biological products [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study of the clinical course of EqPV-H described persistent infection of EqPV-H over five years that resulted in chronic viremia in subclinical horses [14]. Thus, it is plausible that the horse in our case may have been in a subclinical condition, showing chronic viremia, for some time.…”
Section: Discussionmentioning
confidence: 75%
“…However, we could not test for anti-EqPV-H antibodies because there are still few options for antibody detection in the field. In some of the previous papers dealing with EqPV-H [11,14], specific antibodies were measured using luciferase immunoprecipitation systems. However, there are no commercial kits for field testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first isolation of the equine parvovirus in 1985, three equine parvovirus species (EqPVs), which belong to the genus Copiparvovirus and family Parvoviridae, were identified; namely, equine parvovirus-cerebrospinal fluid (EqPV-CSF, 2015), equine parvovirushepatitis (EqPV-H, 2018), and Eqcopivirus (EqCoPV, 2019) [1][2][3][4]. Except for EqPV-H, which is an etiologic agent for equine serum hepatitis [4][5][6][7][8][9][10][11][12][13][14][15], the other two species have not been well investigated.…”
Section: Introductionmentioning
confidence: 99%